The relation between the codification and actual usage of the preposition VIRŠ - Vaičiakauskienė, Sonata (Lietuvių kalba, 2014)
The analysis of Lithuanian syntax phenomena shows that there are many inconsistencies in the actual usage of some cases and prepositions and the codified rules of grammar that apply to them.  This article concentrates on the actual usage of the Lithuanian preposition virš (‘above’) over the last decade. Thus the aim of the article is to discuss the relation between the codified rules of grammar and the current use of the preposition virš and to provide some guidelines in relation to the specification of its codified rules. The analysis of the usage of virš reveals that this preposition is used to refer to some excess in quantity, weight, time, distance, property or characteristic as well as to some overbalance, especially in periodical press. Such usage of the preposition virš is quite frequent both in spoken and written language. Currently, such usage of virš is considered by language standardisers as avoidable or even unacceptable in standard language. Such attitudes of linguists are based on the fact that the usage of virš in the sense of excess is a result of the influence of Slavic languages and dialects. The data of the analysis suggest that the usage of the preposition virš is becoming more common not only due to the above-mentioned reason but also because of the similarity or even overlap between the meanings of constructions used to refer to excess that are standardised and those that are considered to be avoidable. Systemic characteristics of the usage of the preposition virš show that its usage in the sense of excess is not necessarily in conflict with the standard language system. As a result, the pervasive use of the preposition virš in the sense of excess suggests that with regard to language users’ habits but not conflicting with language systematicity, linguists should consider the possibility of standardising the usage of virš in the sense of ‘excess’. Certainly, before anything can be put forward, more research on the usage of the preposition virš has to be carried out.
Keywords: none